2017
DOI: 10.12973/eurasia.2017.00710a
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Teachers’ Professional Knowledge and Competence in Environmental Education

Abstract: The rapid development of technology and economy has largely enhanced the quality of life. Nevertheless, various social and environmental problems have emerged. It would be the key solution to develop environmental education in order to have people present the environmental knowledge and the attitudes and value to concern about the environment and develop the skills and action to solve environmental problems. Environmental education teachers in 25 colleges and universities in central and southern Taiwan are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Aside from this advancement they had, results revealed that they already had a particular interest in the care for the environment, and it is further enhanced as they became a member of the organization. This result is in consonant with the study of Yuan et al (2017). Their research revealed that there is a positive correlation between care for the environment and environmental sustainability.…”
Section: Discussionsupporting
confidence: 84%
“…Aside from this advancement they had, results revealed that they already had a particular interest in the care for the environment, and it is further enhanced as they became a member of the organization. This result is in consonant with the study of Yuan et al (2017). Their research revealed that there is a positive correlation between care for the environment and environmental sustainability.…”
Section: Discussionsupporting
confidence: 84%
“…Another study which agrees with the above correlation is that of Yuan et al (2017) on environmental education teachers from 25 colleges and universities in central and southern Taiwan. Data were collected from 224 valid questionnaires received from 250 distributed.…”
Section: Relationship Betweensupporting
confidence: 69%
“…The empirical research method of accounting mainly including the variable definition, model contribution, data collection and so on (Rebele & Pierre, 2015;Yuan et al, 2017). The authenticity of the data collection, the rationality of the model construction directly determines the objective and fairness of the follow-up empirical research conclusion (Gassen, 2014).…”
Section: Methodsmentioning
confidence: 99%